Integrasi POAC dan Nilai Akhlak Kepemimpinan Islam dalam Manajemen Organisasi Santri di Pondok Pesantren Nurul Abror Serang Banten - Nita Yuniarti; Tambi'un; Wardatul Ilmiah (E-Jurnal Aksioma Ad Diniyyah : The Indonesian Journal of Islamic Studies, 2025)
This study aims to formulate an Islamic value-based student organization management model for leadership development at Pondok Pesantren Nurul Abror Banten. This research employs a qualitative case study approach through in-depth interviews, participatory observation, and documentation. The participants consist of OSKINA (student organization) supervisors, OSKINA student leaders, and active students involved in organizational activities. Data were analyzed interactively through data reduction, display, and conclusion drawing. The findings indicate that the POAC management functions (Planning, Organizing, Actuating, Controlling) are integrated with the values of amanah (trustworthiness), adab (ethical conduct), and the principle of amar ma’ruf nahi munkar as the core characteristics of Islamic leadership. This integration is conceptualized as the Islamic Moral-based POAC (IMPOAC) Model, which consists of: (1) I-Planning: value-based deliberation in program formulation; (2) I-Organizing: a tiered leadership structure based on exemplary behavior; (3) I-Actuating: 24-hour leadership practice within the boarding school environment; and (4) I-Controlling: moral coaching as a form of accountability supervision. The IMPOAC Model contributes to the development of student leadership through the transformation of trustworthiness, discipline, ethical communication, and social manners. This study emphasiz.es that Islamic boarding schools (pesantren) possess a strategic potential to produce morally grounded leaders through structured and value-driven student organization management, which can be replicated in other pesantren or Islamic educational institutions